Indigenous men's pathways to 'living the right kind of life and walking the right path' post incarceration in Canada: understanding the impacts of systemic oppression, and guidance for healing and (w)holistic sexual health. Issue 4 (3rd April 2023) - Rand, Jenny R.; Melro, Carolyn; Biderman, Maya; McMillan, L. Jane; Miller, Arthur Dave; Lekas, Scott; Numer, Matthew
Abstract: Indigenous men around the world hold expertise over their own lives. Informed by this perspective, this study centres this experience to better understand what is needed to improve sexual health outcomes among a group of men with a history of incarceration. Semi-structured interviews were conducted with 10 Indigenous men with such a history. Through thematic analysis the study identified two major themes: 1) the impacts of systemic oppression; 2) the value of guidance in walking the right path. Men identified colonial trauma and the associated mental, physical, emotional and spiritual wounds stemming from systemic oppression as continuing to impact their wellbeing. Men also described the systems of support necessary to help guide them on their journeys through incarceration, rehabilitation and building strong and nurturing relationships. Findings from the study provide important guidance from Indigenous men for future more holistic sexual health intervention programming.